THE RELEVANCE OF STEAM EDUCATION IN PREPARING 21ST CENTURY STUDENTS - Firmansyah Firmansyah; Aslan Aslan (Adisam Publisher, 2025)
STEAM (Science, Technology, Engineering, Arts, and Mathematics) education has significant relevance in preparing students for the challenges of the 21st century. With an approach that integrates various disciplines, STEAM education develops critical thinking, creativity, collaboration, and communication skills that are essential for success in the world of work and everyday life. The contextual and practical learning methods in STEAM also increase student motivation and provide a deep understanding of real-world applications. In addition, the integration of the arts enriches students' innovative abilities and adds a humanistic perspective. Overall, STEAM education equips students with comprehensive technological skills and knowledge, making it an important foundation in shaping a generation that is ready to face complexity and contribute positively in the 21st century.